If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x^2-4=23
We move all terms to the left:
3x^2-4-(23)=0
We add all the numbers together, and all the variables
3x^2-27=0
a = 3; b = 0; c = -27;
Δ = b2-4ac
Δ = 02-4·3·(-27)
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{324}=18$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-18}{2*3}=\frac{-18}{6} =-3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+18}{2*3}=\frac{18}{6} =3 $
| 8t–9=3t+16* | | 2(1.5m+1)=2.5(2m+4) | | 8t–9=3t+16 | | X2+y2=35 | | n-7.5=22 | | -(-x+4)+4x-3=31 | | 2(1.5m)=2.5 | | x2+6=5 | | x2-4=9 | | -6t-12=54 | | 5x2=5 | | n/8=10/16 | | 2x+24=9x+1 | | 4(4x-10)=21 | | 350097/565000=x | | (x+1)^2+4=8 | | 10/6=n/11 | | 5=x*10/250 | | 7x-6+6=20 | | (Z*z)-(5×z)=30 | | -6t-12=24 | | 9d+7d=d | | (2x-3)+(2x+15)=7x-18 | | 17=x+913=x+5 | | -11/x+8=6 | | 1x2=17 | | 17=x+9 13=x+5 | | 7x+6=-x2 | | -1/x+5=12 | | (3x+17)+(3x+11)=11x-7 | | 2*5x-3=24 | | 7x+4x=49 |